The environment as a taxation matrix: the greening of the Brazilian constitutional tax system - Lopes Bindeli, Bárbara; Rahnemay Rabbani, Roberto Muhájir; Carregosa Rabbani, Allívia Rouse (Brazilian Journal of Agroecology and Sustainability, 2024)
Environmental taxation focuses on the possibility of acting as a behavior-inducing norm and presents itself as a viable instrument for environmental protection. Thus, it is necessary to rethink the way in which these instruments are willing to serve sustainability in their multidimensional character, contemplating their legal-political, economic, ethical, and social dimensions. This research applies the deductive method and in an exploratory study, from a bibliographic, legal, and jurisprudential review, to reveal how the protection of the environment can be applied under the guidelines of the Brazilian tax constitutional system, discussing the legal consequences of this process, specifically in the construction of the theoretical bases that support the economic-tax instruments aimed at environmental protection. It presents an approach on the environmental agenda to be applied by the regulatory instruments of the State, to encourage sustainable practices and discourage behaviors that cause degradation to the environment. It is concluded that the existing economic instruments, including environmental taxation, are one of the ways to achieve sustainability.